Penyelesaian Multiple Travelling Salesman Problem (M-TSP) Dengan Menggunakan Algoritme Genetika: Studi Kasus Pendistribusian Barang Di Kantor Pos Lumajang - Anang Hanafi; Randy Cahya Wihandika; Putra Pandu Adikara (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Online buying and selling currently more and more in demand by all societies, the provider of application companies that bring together sellers and buyers also do not stop releasing promotions on every occasion. The increasing of online trading market it caused the rise of goods delivery process. The freight forwarding company also strives to provide the best service in delivery process. The companyy also need to minimize the cost to be made during the shipping process. In the post office company, especially in Lumajang had 4 sales and 16 delivery destinations, the problem is called Multiple Traveling Salesman Problem (M-TSP). This research discussed issues for optimized the distance, weight, and volume of goods to be delivered from the starting point to some point of destination. From the research that had been done in this case by using genetic algorithms optimal parameters were obtained with a population size of 200, the maximum generation of 500, with a combination of crossover rate 0.4 and mutation rate 0.6 and also uses elitism selection methods and the result of fitness was 0,05288.